SEGREGATION OF THE JEWS IN THE GHETTO OF “VOLYN-PODILLIA” GENERAL DISTRICT ACCORDING TO THE MATERIALS OF YACHAD-IN UNUM ORGANIZATION (PARIS, FRANCE) - MYKHALCHUK , Roman (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The research methodology is based on the principles of scientificity, historicism, problem-historical, search methods, as well as the methods of analysis and systematization. The method of oral history, orevidence is a leading one in the research. Scientific Novelty. For the first time in historiography, a separate research focuses on the analysis of the Holocaust oral history sources, orevidences of “Yahad-In Unum” scientific institution regarding the situation of the Jews in the ghetto of “Volyn-Podillia” General District. The life of the Jews in the ghetto has been analyzed from the perspective of non-Jewish testimonies. For the first time, a large number of unpublished oral sources have been introduced into scientific circulation. Conclusions. The analysis of the Yahad-In Unum oral sources, orevidences made it possible to reconstruct the history of the ghetto establishment and functioning in “Volyn-Podillia” General District during the Holocaust from the perspective of non-Jewish testimonies. These sources are valuable because they contain details of the Jewish life in the ghetto and information not found in other official documentary sources. In the study the features of the ghetto establishment, resettlement, everyday life, labour, robbery, physical and moral abuse of ghetto prisoners have been elucidated. The Jews used various methods to survive, interacting with representatives of the occupation administration and civilian residents. Despite the fact that the ghetto functioning has been researched on the example of “Volyn-Podillia” General District, certainly, the research results have a much broader significance for understanding the Nazis’ plans “to solve the Jewish issue”, in particular the segregation of the Jews in ghettos on the territories occupied by Germany. Key words: Yahad-In Unum, the Holocaust, video testimony, oral history, orevidence, ghetto, Patrick Debois, “Volyn-Podillia” General District.